Minimally Invasive Endocrine (Thyroid, Parathyroid, Adrenal) Surgery: Evolution of Operative Techniques, Safety, Effectiveness and Outcomes - Christakis,I; Constantinides,V; Garas,G; Joseph,J; Tolley,N; Palazzo,F (2014)
The field of endocrine surgery has seen significant changes over the last 10 years. New surgical techniques in thyroid, parathyroid and adrenal surgery characterised by reduced trauma of access and new technology have heralded minimally invasive techniques that have allowed surgeons to perform operations with results similar to traditional approaches whilst offering advantages in recovery time and cosmesis. Surgery is the only definitive cure for primary hyperparathyroidism(PHPT). Sir John Bland Sutton performed the first recorded parathyroidectomy sometime before 1917 but it is Felix Mandl who in 1925 performed the first successful parathyroidectomy for hyperparathyroidism. The surgical strategy for the identification and safe removal of the diseased parathyroid glands has evolved into a safe effective technique with a high success rate in experienced hands. However the arrival of new imaging and surgical technology, an increased understanding of the surgical anatomy and the accumulated experience have been the drivers for developing minimally invasive techniques. Bilateral neck exploration(BNE) with visualisation of all 4 parathyroid glands remains the gold standard treatment of PHPT but only in cases where the localisation studies do not conclusively localise the disease or in cases of persistent or recurrent hyperparathyroidism. Most parathyroidectomies are performed by one of a number of minimally invasive techniques. Such techniques include the endoscopic approach which offers the benefits of magnification, the minimally invasive videoscopically/endoscopically assisted parathyroidectomy (MIVAP) which offers the advantages of the endoscopic approach via a gasless central approach. The focused lateral mini-incision parathyroidectomy is probably the most widely used since it requires no additional instruments, is quick and can be performed under local anaesthetic with equivalent success rates to the other techniques and similar results to the BNE in patients who